China STudy of valsartan/amlodipine fixed-dose combination-bAsed long-Term blood pressUre management in HypertenSive patients: a one-year registry (China STATUS III). (3rd August 2019) - Huo, Yong; Gu, Ye; Ma, Genshan; Guo, Jincheng; Xiong, Longgen; Luo, Zhurong; Xie, Jianhong; Li, Weimin; Zhao, Jianrong; Yan, Xiaowei; Liu, Wei; Xu, Yawei; et al.
Abstract: Objective: The present observational study evaluated long-term management of hypertension in patients who received treatment with valsartan and amlodipine in a single-pill combination (Val/Aml SPC) in a real-world setting in China (Chinese Clinical Trial Registry number ChiCTR1900021324). Methods: This was a prospective, observational, multicenter, real-world registry study wherein patients with hypertension who had already received Val/Aml SPC (80/5 mg) for at least 4 weeks before study enrollment were observed for 1 year. Investigators recorded patient data every 3 months and essentially five times during the 1 year follow-up period. Effectiveness was assessed by the blood pressure (BP) control rate and average duration of treatment at the end of the study. Safety was monitored by the incidence of adverse events (AEs) and serious adverse events (SAEs). Results: Overall, 985 patients were enrolled (mean ± standard deviation [SD] age: 60.3 ± 11.5 years); of these, 894 were included in the full analysis set, 758 of whom completed the study. At baseline, BP was controlled (<140/90 mmHg) in 64.3% of patients on Val/Aml SPC for at least 4 weeks before enrollment. Office BP control rates significantly improved from baseline in 74.1% of patients at 1 year ( p  < .0001). Overall, 575 (87.0%) patients remained on Val/Aml SPC at 1 year (average exposure: 311.5 days). AEs were reported in 23.3% of patients. The majority of AEs were mild to moderate, and 0.6% of patients discontinued Val/Aml SPC because of SAEs. Conclusion: This study provides evidence that Val/Aml SPC effectively reduced BP over the long term among Chinese hypertensive patients, with a good adherence and tolerability profile, and that most hypertensive patients may benefit from this combination. Trial registration: Chinese Clinical Trial Registry identifier: ChiCTR1900021324.